Analisis Strategi Copycat Global Brand Terhadap Niat Beli Konsumen Studi Eksperimental pada Gen Z dan Milenial di Surabaya - Galuh Anandata; Agung Krispimandoyo; Muhammad Saiful Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Copycat strategies are increasingly used by local brands to leverage global brand associations to influence consumer purchase intentions. However, the effectiveness of this strategy depends on the product context and the form of imitation used. This study aims to analyze the influence of product type (utilitarian vs. hedonic) and copycat strategy (attribute vs. theme) on purchase intention, as well as to test the potential interaction effect between the two factors. The study used a 2 × 2 factorial experimental design with a quantitative approach. Data were collected through a survey of 400 Generation Z and Millennial consumers in Surabaya who were exposed to copycat product stimuli. Data analysis was performed using Analysis of Variance (ANOVA). The results showed that product type and copycat strategy independently had a significant effect on purchase intention. However, no significant interaction effect was found between product type and copycat strategy. This finding indicates that the influence of these two variables on purchase intention works separately without forming a combined effect.